STREAMLINING ONLINE DISPUTE RESOLUTION WITH ALTERNATE DISPUTE RESOLUTION”: CHANCES AND CHALLENGES - Dr Rakhi Singh Chouhan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Alternative ways of resolving the disputes are always the best ways to resolve the disputes. It has its own benefits of cost, technology, time and satisfaction. The time is demanding change in the ways we interact with each other, which in turn is changing the way we resolve our disputes. Every society throughout history has crafted social institutions to resolve problems fairly and consistently, and that is true also for the online society we are building on the Internet. Online dispute resolution (ODR) is the study of how to effectively use technology to help parties resolve their disputes. Recently Niti Ayog initiated the online dispute resolution. Originally crafted by companies like eBay to promote trust in eCommerce, ODR is now being integrated into the courts to expand access to justice and reduce costs. With the expansion of artificial intelligence and machine learning, ODR has the potential to become the new default for fast and fair resolutions, but there are many questions that still need to be answered, and much potential for fraud and abuse. This study is to evaluate the practical feasibility of ODR in context of its parent concept of ADR. During covid, the necessity of ODR was felt more to be implemented to make the resolution system faster than even ADR